The quest for fire ; a novel of prehistoric times - Rosny, J.-H., aîné, 1856-1940 (Pantheon Books, 1967)
Two rival warriors of a prehistoric tribe set off on a dangerous and distant search for fire, an element essential to tribal unity and leadership.